The Pros and Cons of Full Dollarization - Borensztein, Eduardo (IMF Working Papers; Working Paper ;, 2000)
We analyze the costs and benefits of full dollarization compared to its closest alternative, a currency board, quantifying for Argentina where possible. Potential advantages include lower borrowing costs and deeper integration into world markets. One cost is the transfer of seigniorage to the United States. The country may also lose the 'exit option' to devalue in the face of major shocks. Similarly, even a country with a currency board may lose some ability to act as lender of last resort to the banking system. We review how various country characteristics influence the balance of arguments.